Demokrasi Bottom-up dalam Penganggaran di Porto Alegre: Peran Kelompok Masyarakat dalam Tata Kelola Anggaran Daerah - Nabila Fitria Ariyanti; Averina Shalva; Fayza Arzmy Niafaran; Ridwan; Gema Pertiwi (QAWIUN : Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the mechanism of participatory budgeting (PB) in Porto Alegre, Brazil, as a bottom-up democracy model in regional budget governance. Using a qualitative descriptive-analytical approach based on library research and guided by the Empowered Participatory Governance (EPG) framework, this study addresses three main questions: (1) how PB operates in Porto Alegre, (2) the role of community groups in the process, and (3) the factors that support and hinder its implementation. The findings indicate that Porto Alegre's PB operates through an annual deliberation cycle across 16 budget districts, granting citizens, especially the urban poor, real authority to determine public spending priorities through a devolved, multi-tiered forum structure. Civil society groups, including neighborhood associations, labor organizations, women's groups, and urban movements, serve as key driving actors that mobilize participation, channel aspirations, monitor implementation, and uphold the integrity of the deliberative process. Key supporting factors include the political commitment of the Partido dos Trabalhadores, strong civil society organizational capacity, inclusive institutional design, and growing public trust. Meanwhile, dependence on political leadership, unequal capacity among groups, fiscal constraints, and the potential for de-democratization became obstacles that weakened PB's sustainability after 2004. These findings have significant implications for strengthening citizen participation mechanisms in the context of Musrenbang in Indonesia.